BIO-LINGUISTICS: PORTRAYING YOUNG FARMERS’ ACQUISITION ON ORGANIC FARMING TERMINOLOGIES - Ida Bagus Nyoman Mantra; Dewa Ayu Puspawati; Ida Ayu Made Sri Widiastuti; Nengah Dwi Handayani (Unmas Press, 2021)
The covid-19 outbreak has widely changed the way of life for many people due to the limitation of crowd social contact. Young workers have to think harder to find employment meanwhile many industries including the tourism industry were closed. Farming suddenly becomes an attraction for young people to explore their opportunities for survival and fulfill their need for food. This phenomenon brightens the future of farming because young farmers certainly have more capability in developing the farming industry by utilizing modern applicable technology and develop farming products to supply the needs of the global market. This study explored the young farmers’ acquisition of organic farming since this farming becomes a new trend that has many befits for the future of farming and the health of the land. The study revealed that young farmers' acquisition of organic farming terminologies was insufficient, therefore the study implies that the young farmers should continually develop their ability in organic farming.